Identification of QTL for resistance against two fungal pathogens, Pyrenophora teres f. teres and Bipolaris sorokiniana, in a barley (Hordeum vulgare L.) diversity set - Novakazi, Fluturë (2023)
Barley is worldwide the fourth most important cereal crop and is cultivated in near desert to sub-arctic conditions. The majority of production, around 70 %, is used for animal feed, 20 % are used for malting and the rest for human consumption, with regional differences.Pests and diseases constantly result in high yield losses. Two worldwide important fungal foliar diseases of barley are Pyrenophora teres f. teres (Ptt) and Bipolaris sorokiniana (Bs), the causal agents of net blotch and spot blotch, respectively. Yield losses are on average around 40 % and can amount to over 70 % in years with epidemics. Both pathogens are highly variable and the occurrence of new pathogenic strains demands for breeding of resistant cultivars.In order to identify new resistance sources, a diverse barley set comprising 449 accessions originating from over 50 different regions all over the world, expressing different levels of resistance against both pathogens, was screened. Seedling resistance was tested under controlled greenhouse conditions with three isolates of each pathogen. Adult plant resistance was tested in field trials at three and two locations for Ptt and Bs, respectively. Phenotypic results showed a wide range of the level of resistance and significant differences between accessions were observed in all trials. The set was genotyped using the Illumina iSelect 50k barley SNP chip. After filtering for quality control parameters, i.e. failure rates < 10%, heterozygous calls < 12.5% and minor allele frequency > 5%, 33,318 polymorphic, mapped SNPs were left for further genome-wide association studies (GWAS). Markers were mapped against the barley reference sequence. GWAS was conducted using a compressed mixed linear model (CMLM) including population structure and kinship matrix. GWAS for Ptt revealed 254 significant marker-trait associations (MTAs) located on chromosomes 3H, 4H, 5H, 6H, and 7H and corresponding to 15 quantitative trait loci (QTL). Four of these loci are putatively new and were not previously ...